2014
DOI: 10.1179/1973947814y.0000000200
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid and arsenic trioxide induce apoptosis and modulate intracellular concentrations of calcium in hepatocellular carcinoma cells

Abstract: We investigated the effects of all-trans retinoic acid (ATRA) and arsenic trioxide (ATO), alone and in combination, on apoptosis and intracellular calcium concentration in hepatocellular carcinoma (HepG2) cells. We used HepG2 cells to test the effects of ATRA and ATO, individually and in combination, on cell proliferation, apoptosis, and intracellular-free calcium concentration. The results indicate that each drug decreased cell proliferation, increased apoptosis, and increased intracellular-free calcium in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It has also been recommended as a frontline therapy in advanced HCC by the Chinese Society of Clinical Oncology. Recent studies have demonstrated that ATO can suppress HCC cells through various mechanisms in vitro, such as suppressing proliferation [ 17 , 18 ], retarding invasion and migration [ 19 , 20 ], and reversing multidrug resistance [ 21 , 22 ]. These versatile effects imply that ATO may be suitable for the eradication of residual tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been recommended as a frontline therapy in advanced HCC by the Chinese Society of Clinical Oncology. Recent studies have demonstrated that ATO can suppress HCC cells through various mechanisms in vitro, such as suppressing proliferation [ 17 , 18 ], retarding invasion and migration [ 19 , 20 ], and reversing multidrug resistance [ 21 , 22 ]. These versatile effects imply that ATO may be suitable for the eradication of residual tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…The natural anti-cancer compound, ATRA, has been extensively investigated for the prevention and treatment of cancer, predominantly because of its ability to induce apoptosis in cells derived from various human cancers including APL, hepatoma, breast cancer, lung cancer, and head and neck cancer [ 9 , 11 , 12 , 50 , 51 ]. The present study also showed that ATRA induced apoptosis in human hepatoma cell lines, including HepG2 and Huh7, by activating the p53-dependent apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable interaction between the above compounds in cell cultures. Arsenic trioxide induced apoptosis is enhanced by ascorbate, docosahexaenoic acid, genistein, quercetin, retinoic acid (Michel et al 2003;Baumgartner et al 2004;Sanchez et al 2009;Shen et al 2012;Wei et al 2014) and ameliorated by resveratrol (Chen et al 2015). cAMP prevents apoptosis induction by palmitate, docosahexaenoic acid, arsenic trioxide and doxorubicin, in different cell lines, by promoting phosphorylation of PKA target proteins and the cAMP-GEF pathway (Kwon et al 2004;Miura et al 2005;Safa et al 2014;Fatemi et al 2015).…”
Section: Modulators Of Apoptosismentioning
confidence: 99%